миллий ва умуминсоний қадриятларимиз таълим-тарбия асоси сифатида - Сададдинов, У.У. (SCIENCE and SOCIETY, 2023)
The article devotes to the system of spiritual and moral values of customs and integrative description as a cultural phenomenon. Description of natural and universal traditions , importance of a certain level of assimilation and moral standards in modern conditions.
Keywords: spiritual and moral values; students; personality; norm; education; upbringing